Precocious puberty: associated conditions - Celso Junior Wanderley Cavalcante; Luciano Lima Correia; Durval Damiani (Universidade de Fortaleza, 2014)
Objective: To analyze the characteristics of children with central precocious puberty (CPP), identifying both their clinical and epidemiological characteristics, as well as the determinants for receiving timely specialized health care. Methods: Cross-sectional retrospective study with analytical approach of 342 medical records of children aged 1 to 11 years with CPP, from the Endocrinology Outpatient Clinic of a reference hospital. Biological, socio-economic, family and nutritional data of the 1994 to 2010 period was submitted to univariate and bivariate analysis, using the chi-square test for the statistical evaluation of the associations. Results: The main features of children with CPP were: being adopted, 25 (7.3%); being overweight, 92 (27.1%); being obese, 85 (25.1%); initiating puberty before six years of age, 205 (60.3%). Children with PPC who received late specialized care were the ones who most precociously presented signs of puberty (p<0.001), and belonged to families with lower income (p<0.002). Conclusion: High proportions of children with CPP were adopted and presented overweight/obesity. Children with excessively early onset of puberty signs, and belonging to low income families, suffered significant delay in obtaining specialized care. doi:10.5020/18061230.2014.p153